2013
DOI: 10.5888/pcd10.120135
|View full text |Cite
|
Sign up to set email alerts
|

Support Among Middle School and High School Students for Smoke-free Policies, North Carolina, 2009

Abstract: IntroductionIn the United States, little is known about youth attitudes toward smoke-free policies. Our research measures North Carolina middle school and high school students’ opinions about smoke-free policies in indoor and outdoor public places as well as private places such as vehicles, homes, and work environments.MethodsData come from the 2009 North Carolina Youth Tobacco Survey. The overall middle school response rate was 79.2% (n = 3,805 students); the overall high school response rate was 78.2% (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Levels of support for smoke-free public places typically vary by smoking status, knowledge about the harmfulness of SHS, and demographics [ 18 , 20 22 , 31 , 32 ]. Levels of support also vary by the type of restriction [ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of support for smoke-free public places typically vary by smoking status, knowledge about the harmfulness of SHS, and demographics [ 18 , 20 22 , 31 , 32 ]. Levels of support also vary by the type of restriction [ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been more mixed findings about educational attainment; in some studies, lower educational attainment has been positively associated with supportive policy attitudes [ 18 , 21 ] although other studies have found no association [ 17 ], or contrary findings [ 20 , 22 ]. Smoking behavior has been consistently associated with policy attitudes such that nonsmokers tend to hold more favorable attitudes towards tobacco control policies than smokers [ 17 , 18 , 19 , 20 , 21 , 23 ]. With respect to beliefs, political ideology may impact attitudes, such that favorable attitudes towards tobacco control decreased as individuals showed more conservative political views and had less knowledge of tobacco’s health impacts.…”
Section: Introductionmentioning
confidence: 99%
“…The current research examines attitudes toward four potential new Federal tobacco regulations (banning menthol from cigarettes, reducing nicotine levels in cigarettes, banning candy and fruit flavored electronic cigarettes, and banning candy and fruit flavored little cigars and cigarillos) and associations of such attitudes with several factors. Previous research has measured attitudes towards various tobacco control measures, including smoke-free policies [ 19 , 20 , 23 , 24 ], point of sale policies [ 17 , 25 ], raising the age of tobacco use [ 26 ], banning menthol in cigarettes [ 18 , 21 , 27 ], reducing nicotine content in cigarettes [ 28 ], and banning flavored e-cigarettes [ 29 , 30 ]. The current research extends previous work by simultaneously assessing a range of factors, including trust in government, knowledge and credibility beliefs about the FDA, exposure to tobacco control communication campaigns, and state-level variables that may influence attitudes across a diverse group of potential new tobacco control policies, using a nationally representative sample of U.S. adults.…”
Section: Introductionmentioning
confidence: 99%
“…Current smoking was investigated by asking students the following question: “How many days did you smoke cigarettes during the past 30 days?” Responses were defined as current smokers when the selected answers indicated 1 or more days [41]. Current drinking was assessed with the following question: “During the past 30 days, on how many days did you drink alcohol?” Responses were defined as current drinkers when the selected answers indicated 1 or more days [42].…”
Section: Methodsmentioning
confidence: 99%